Assessment of trastuzumab use in adjuvant therapy. Issue 2 (12th March 2012) - Alcobia, A.; Leandro, A.; Domingos, S.; Costa, G.; Branco, V.
Abstract : Background: Trastuzumab is indicated for the treatment of patients overexpressing HER2 in metastatic breast cancer and HER-positive early breast cancer. Purpose: This study aimed to evaluate the use of trastuzumab in an adjuvant setting, in the Hospital Garcia de Orta. Materials and methods: This evaluation, carried out in September 2011, included all early-stage breast cancer patients who started trastuzumab in 2008 or 2009. Data source: medical records and patients' prescriptions from the cytostatic unit in the pharmacy department. Each patient was evaluated on six factors of poor prognosis (age < 50 years; invasion of lymph nodes; absence of oestrogen and progesterone receptors; tumour size > 2 cm; disease staging ≥ GIII and overexpression of the HER2 receptor). Results: This study included 32 women with an average age of 49.5±11.4 years (33-75 years). Twenty-five women were clinically well (78.1%), 2 (6.3%) had metastases and 5 (15.6%) died. All patients had at least one factor of poor prognosis (over-expression of HER2). Only 1 patient had 1 poor prognosis factor, 6 had two factors of poor prognosis, 12 patients had 3, 9 patients presented 4 and 4 patients had 5 factors for poor prognosis. Statistically significant differences were found between the patients who were clinically well and those who developed metastatic disease or died, for the number of poor prognosis factor present at the time of trastuzumab prescription (p<0.05). Of all the poor prognosis factors, disease staging was the one that showed statistically significant differences between the 2 groups of patients (p<0.001). Conclusions: The literature refers to disease staging as the most accurate estimate of prognosis in breast cancer. Based in our study, disease staging was also the factor of prognosis that best predicted the result of trastuzumab therapy.